Diphtheria and Pertussis: A Literature Review of Two Preventable Infectious Diseases - Sabrina, Khansa Aulia; Rahmawati, Fadila; Aghni, Hasna Tazkia; Siregar, Chivan Agustinus (Jurnal Biologi Tropis, 2025)
Diphtheria and pertussis are dangerous infectious diseases that infect the respiratory tract. Both diseases are caused by bacteria that can affect people of all ages, especially infants and children. The research design used was a literature review. Data sources were obtained by conducting electronic searches through library search engines including PubMed, ScienceDirect, MDPI, and Google Scholar to find journal articles and guidelines discussing diphtheria and pertussis. The findings indicate that diphtheria and pertussis are respiratory infections caused by bacteria. These diseases are transmitted through respiratory droplets and can spread very quickly. Both diseases remain a public health challenge due to their significant morbidity and mortality rates, especially in vulnerable groups such as infants and children. Prevention efforts need to be integrated with early detection of clinical manifestations and diagnosis, appropriate case management, and public education regarding diphtheria and pertussis prevention through timely vaccination and maintaining high vaccination coverage.